An empirical inquiry to psychological variables constituting stress: middle aged widows in rural communities in Nigeria (2014)
This study investigated empirically the psychological variables constituting stress among middle aged widows in rural communities in Nigeria. The participants were 128 widows drawn from Kajola, Itesiwaju, Saki East, and Saki West local government of Oyo state in Nigeria. The instrument used for gathering information was the Widowhood Stress Scale (WSS), developed by the researchers. A descriptive research design was adopted for this study, with two research questions raised as a guide and the use of Multiple Regression Anaylsis as the statistical tool for processing the data collected. The result indicated that four psychological variables constitute widow's stress level in the rural communities of study.